Melanoma múltiplo primário no serviço de dermatologia do hospital das clínicas da UFMG - Ana Francisca Junqueira Ribeiro Pereira (2011)
Background: Patients with previous diagnosis of cutaneous melanoma are more susceptible to other primary melanomas than the general population. Frequency of multiple primary melanomas (MPM) varies from 1,2% to 8,6% in the literature. Because of the increasing incidence of melanoma in the world and better survival, a growing number of patients are expected to be at risk of developing MPM. Most of the studies on MPM have been performed with Caucasian population outside Brazil. The aim of this study is to analyze the frequency and the features of MPM seen at the Pigmented Lesions Unit of Federal University of Minas Gerais University Hospital, Brazil. Methods: Data from 160 patients with diagnosis of cutaneous melanoma from 1990 to 2010 were analized. For the purpose of MPM estimation, final date of follow up was either the date of the last medical visit or the date of death. Patient and tumor characteristics were compared between MPM and solitary melanoma groups. A survival analysis model in which the event was the development of a second primary melanoma was designed in order to identify possible features related to the occurrence of MPM. Results: From 160 patients, 19 (11.9%) developed MPM. Most (73.7%) of MMP patients were females. Six (33.3%) MPM patients had a positive family history of melanoma and 38.9% had atypical nevi. First and second melanomas were synchronous in five (26.3%) out of 19 cases. In 15 (78.9%) out of 19 MMP patients, the second melanoma occurred within the first three years of follow-up. In 14 (73.7%) patients, the second primary melanoma was located in the same anatomic region of the first tumor. There were 82 melanomas in 19 MPM patients with an average of 4.3 melanomas per patient. The average follow-up time was 4.7 years. The average time interval between the first and the second melanomas was 28.3 months. The average age at first diagnosis in the MPM group was 47.4 years, almost 10 years smaller than in single melanoma group (56.0 years). Of the MPM, 54.2% were located on the trunk, 50.8% were superficial spreading melanomas and 76.7% were in situ. Survival rates of MPM patients and single melanoma patients were not statistically different. Conclusion: In this series, a MPM frequency of 11.9% was found. The majority of patients with MPM were females. Among MPM ndividuals, presence of atypical nevi and/or family history of melanoma were morefrequent than in single melanoma group. MPM predominated in the trunk and the superficial spreading subtype was the most common. Most MPM were in situ and survival rate was similar in both groups. The results highlight the importance of close life-long follow-up of melanoma patients, due to the risk of MPM and disease recurrence